Machine learning-based predictive models and drug prediction for schizophrenia in multiple programmed cell death patterns - Feng, Yu; Shen, Jing (Frontiers in Molecular Neuroscience, 2023)
Background: Schizophrenia (SC) is one of the most common mental illnesses. However, the underlying genes that cause it and its effective treatments are unknown. Programmed cell death (PCD) is associated with many immune diseases and plays an important role in schizophrenia, which may be a diagnostic indicator of the disease.